Use of biologics for psoriasis in Central and Eastern European countries. (14th September 2015) - Rencz, F.; Kemény, L.; Gajdácsi, J.Z.; Owczarek, W.; Arenberger, P.; Tiplica, G.S.; Stanimirović, A.; Niewada, M.; Petrova, G.; Marinov, L.T.; Péntek, M.; Brodszky, V.; et al.
Abstract Objectives To evaluate the use of biological agents for the treatment of psoriasis and to explore country‐specific differences within six Central and Eastern European (CEE) countries, namely Bulgaria, Croatia, the Czech Republic, Hungary, Poland and Romania. Methods A literature overview on the epidemiology and disease burden of psoriasis in CEE was conducted. The number of patients treated with biologics was obtained from patient registries, ministries of health, national professional societies and health insurance funds. Biological treatment rates were estimated by two different methods: (i) as a proportion of all psoriasis patients of a country (assuming a common prevalence of psoriasis 2%) and (ii) per 100 000 population. Moreover, we provide a detailed comparison of drug coverage policies and guidelines regulating the treatment with biologics in psoriasis. Results On average 0.25% of all psoriasis patients, or five psoriasis patients out of 100 000 inhabitants are treated with biologics embedding a 14.6‐fold difference between the six countries. Bulgaria, Croatia and Poland lag behind the other three countries in the use of biologics. The significant differences among CEE countries cannot be explained by variations in prices of biologics, cost‐effectiveness or budget impact of biologics. It seems that the time since coverage decision, the fewer number of covered biologics, the more restrictive criteria to be eligible for covered treatment in terms of baseline Psoriasis Area and Severity Index and Dermatology Life Quality Index scores, and the maximum duration of treatment allowed are responsible for the majority of the differences. Conclusions There exists a disconnect between the European psoriasis treatment guidelines and the various CEE country‐specific biologic coverage eligibilities. The cost of biologic therapy for psoriasis is not solely and directly responsible for the different use rates amongst the CEE countries. Psoriasis may not be perceived by all payers as a serious disease that can be successfully treated in a cost‐effective manner.